Pengelolaan Sampah Di Masa Pandemi - WIDYASTUTI, SRI; Joko Sutrisno; Yoso Wiyarno (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
The Covid-19 pandemic has changed people's perspectives and behaviour in many ways, especially those related to health and the environment, especially in waste management. Waste management in the community that has been managed by the Trash Bank has also experienced congestion because generally, the managers (officers) do not dare to come into direct contact with garbage. As a result, waste piles up is not managed correctly and becomes a source of disease. Community service aims to provide socialisation and practice of standard operating procedures (SOP) for waste management during a pandemic. The method used is socialisation and exercise according to the SOP for Waste Management during the pandemic, including making hand sanitisers. The results obtained are that the community is no longer worried about waste management activities such as sorting waste and depositing dry waste to the Garbage Bank.